2005
DOI: 10.1111/j.1538-7836.2005.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor anticoagulation quality in the first 3 months after unprovoked venous thromboembolism is a risk factor for long‐term recurrence

Abstract: unprovoked venous thromboembolism is a risk factor for long-term recurrence. J Thromb Haemost 2005; 3: 955-61.Summary. Background and Aim: Several factors are associated with an increased risk of recurrent venous thromboembolism (VTE). The aim of the study was to investigate whether the quality of oral anticoagulation therapy (OAT) is a long-term risk factor for recurrence of VTE after OAT interruption. Methods and results: A total of 297 patients (170 males) with a recent acute unprovoked VTE episode were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 33 publications
5
61
0
1
Order By: Relevance
“…Recall that we defined "low INR" as Յ1.5-a level of underanticoagulation clearly associated with patient harm. [22][23][24] Nevertheless, we found that the median time until a next INR test was 8 days, and the median time until a next in-range INR value was 16 days. These values themselves are not alarming, but the 75th percentile for each (14 and 30 days) indicate that for a considerable proportion of patients in our dataset, low INR was addressed without a particular sense of urgency.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Recall that we defined "low INR" as Յ1.5-a level of underanticoagulation clearly associated with patient harm. [22][23][24] Nevertheless, we found that the median time until a next INR test was 8 days, and the median time until a next in-range INR value was 16 days. These values themselves are not alarming, but the 75th percentile for each (14 and 30 days) indicate that for a considerable proportion of patients in our dataset, low INR was addressed without a particular sense of urgency.…”
Section: Discussionmentioning
confidence: 71%
“…Some studies have demonstrated that low INR is associated with attenuation of the protective effects of anticoagulation therapy, as would be expected. 7,[22][23][24] Although we know that low INR increases the risk of thromboembolism, relatively little is known about the epidemiology of low INR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…70 The importance of maintaining good control of the INR within the therapeutic range to prevent thrombotic recurrences and bleeding complications has been demonstrated in the setting of treatment for stroke 71 and VTE. 72 A consensus statement from the Anticoagulation Forum on the delivery of optimized anticoagulant care has identified and made recommendations on the following 9 key areas: (1) qualifications of personnel, (2) supervision, (3) care management and coordination, (4) documentation, (5) patient education, (6) patient selection and assessment, (7) laboratory monitoring, (8) initiation and stabilization of warfarin therapy, and (9) maintenance therapy. 73 It has been noted, though it seems to be very uncommon, that a small proportion of commercial preparations of thromboplastins may be affected by LA from certain patients, prolonging the prothrombin time (PT), leading to an overestimation of the actual degree of anticoagulation when PT-INR is used for monitoring.…”
mentioning
confidence: 99%
“…When the primary end-points of recurrent VTE and major bleeding were assessed, there were three events among the 103 [133,134]. Poor-quality INR control, as assessed by the percentage of time with INR <1.5, is associated with a long-term higher risk of recurrent VTE after eventual anticoagulant cessation (RR, 2.7; 95% CI, 1.39-5.25; P=0.003) [135]. NOACs, such as dabigatran and rivaroxaban, directly inhibit thrombin or factor Xa, respectively.…”
Section: Recommendationsmentioning
confidence: 99%